FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN ANEMIA PADA IBU HAMIL TRIMESTER III DI KECAMATAN KAMPUNG MELAYU KOTA BENGKULU TAHUN 2017 - Sari, Eka Ratna; Andriani, Lusi; Kurniawati, PS. (Politeknik Kesehatan Kemenkes Bengkulu, 2018)
Anemia in pregnancy is a condition of pregnant woman with hemoglobin (Hb) <11 gr% in the first and third trimesters while in the second trimester hemoglobin level <10,5 gr%. World Health Organization (WHO) in 2012, reported that the prevalence of anemia in pregnant women in the world ranges an average of 14%, in industrialized countries 56% and in developing countries between 35% -75%. This study aims to determined the factors of the occurrence of anemia in third trimester pregnant women in Kampung Melayu sub-district Bengkulu City 2017. This research uses Analytical Survey design with Cross Sectional Approach. Population in this research is third trimester pregnant woman in Kampung Melayu sub-district as many as 106 people, using sample total sampling technique. The analysis used Chi square test with significance level p <0,05.The results of this study indicate that there is a relationship between adherence of Fe (p = 0,000) and knowledge (p = 0,000) with anemia occurrence in third trimester pregnant women, no relationship between age (p = 0,346), parity (p = 0,949) , Education (p = 0.198), occupation (p = 1,000) with anemia and the most dominant factor with anemia was the consumption of Fe tablet (OR = 78,803). Health workers are expected to provide routine counseling on the causes, symptoms, and effects of anemia for pregnant women and screening anemia by checking Hb at least twice during pregnancy.